Information Proccessing And Its Implication To Teaching and Learning - Yahaya, Azizi (2008)
Learning depends on thinking. The more we can understand what happens when we think, the more we can help other people to think â€œbetterâ€?, differently or in new ways and the more chance we have of being able to help people to learn more efficiently. In the past there has been a growing acceptance that we cannot just ignore thinking simply because we cannot see it happening. Rather, we need to understand what happens when people think and, in the context of educational psychology, try to find ways of helping them to think in ways which will help them to learn more efficiently and easily.